Innovation in Facility Layout Optimization through Heavy Equipment Repair revolution: Inovasi dalam Optimalisasi Tata Letak Fasilitas melalui revolusi Perbaikan Alat Berat - Prediansyah, Mochamad Afan Wahyu; Cahyana , Atikha Sidhi (Indonesian Journal of Innovation Studies, 2024)
This study addresses the challenge of prolonged forklift repair times at PT Karya Mitra Teknik, a heavy equipment repair company, attributed to inefficient facility layout. Through field observations and stakeholder interviews, Activity Relationship Chart (ARC) and Analysis Allocation Diagram (AAD) methods were applied to identify inefficiencies and propose layout improvements. Results show a significant reduction in total repair area distance from 110 meters to 55 meters, indicating enhanced operational efficiency. The findings underscore the importance of optimizing facility layout in heavy equipment repair workshops to streamline operations and reduce repair turnaround times, offering practical implications for similar industries seeking cost-effective solutions. Highlights: 1. Efficient facility layout reduces repair area distance.2. ARC and AAD methods streamline resource allocation.3. Optimal layout enhances operational efficiency, reduces turnaround times. Keywords: Facility Layout Optimization, Heavy Equipment Repair, Operational Efficiency, Activity Relationship Chart (ARC), Analysis Allocation Diagram (AAD)